2021
DOI: 10.3390/su13095095
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Providers’ Continuance Intention of Participation in the Sharing Economy: A Moderated Mediation Model

Abstract: The sharing economy has evolved into a promising business concept that enables individuals to share their idle resources, improving resource utilization efficiency commercially. Recently, it has gained enormous academic attention. However, little concern has been given to the behavior of individual providers on the supply side. This paper aims to uncover the motivational and trust-based providers’ continuance intention of participation in the context of peer-to-peer ride-sharing services. Based on the survey d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 92 publications
0
16
0
Order By: Relevance
“…In a cross-country study, monetary motives positively influence the intention to provide accommodation in Turkey, however its influence on intentions in Lithuania was not significant (Urbonavicius & Sezer, 2019). Economic benefits seem to positively affect the provider's intention to engage (Wilhelms et al, 2017;Raza et al, 2021) and continue to participate (Jiang et al, 2021) in peerto-peer ride-sharing services. In the case of C2C accommodation sharing platforms' financial benefits seem to be the initial drive of becoming a provider (Ikkala & Lampinen, 2015;Lang' et al, 2022) and they positively impact provider attitudes to supply CC platform (Sung et al, 2018).…”
Section: Economic Motivesmentioning
confidence: 86%
See 1 more Smart Citation
“…In a cross-country study, monetary motives positively influence the intention to provide accommodation in Turkey, however its influence on intentions in Lithuania was not significant (Urbonavicius & Sezer, 2019). Economic benefits seem to positively affect the provider's intention to engage (Wilhelms et al, 2017;Raza et al, 2021) and continue to participate (Jiang et al, 2021) in peerto-peer ride-sharing services. In the case of C2C accommodation sharing platforms' financial benefits seem to be the initial drive of becoming a provider (Ikkala & Lampinen, 2015;Lang' et al, 2022) and they positively impact provider attitudes to supply CC platform (Sung et al, 2018).…”
Section: Economic Motivesmentioning
confidence: 86%
“…Study by Sung et al (2018) found that provider's attitude toward Airbnb affects the intention to use this platform. Attitudes toward the sharing economy significantly affect providers' intention to continuously participate in peer-to-peer ride-sharing services (Jiang et al, 2021). Based on a review of past research, the authors assume that the attitude toward CFC positively affects behavioral intention, and propose the following hypothesis.…”
Section: Attitudementioning
confidence: 99%
“…3.2.1 Social factors. Shared economy presents an opportunity to forge new connections and relationships (Jiang and Rui Feng, 2021). Through direct human-to-human contact and the shared experience of exchanging goods, interpersonal relationships are formed and nurtured within the sharing economy (Li and Wen, 2019).…”
Section: Setting Of Criteria and Sub-criteriamentioning
confidence: 99%
“…The concept of sustainability, which emphasizes the responsible and productive use of resources without compromising future needs, has been linked to the idea of the sharing economy Gupta and Racherla, 2018;Heinrichs, 2013). In line with SDT, sustainability is considered an intrinsic motivation, further emphasizing the continuity between sustainable practices and the adoption of the sharing economy (Hamari et al, 2016;Jiang and Rui Feng, 2021;Garg et al, 2022).…”
Section: Setting Of Criteria and Sub-criteriamentioning
confidence: 99%
See 1 more Smart Citation